Accelerating Asian option pricing on many‐core architectures. (26th November 2015) - Li, Shuo; Lin, James
Summary: In this paper, we start by looking at the algorithms and the numerical methods of pricing one exotic option, the strong path dependent Asian option using the Black–Scholes pricing model. We cover both geometric average and arithmetic average schemes that lead us to two different numerical solutions. Next, we discuss how to implement these algorithms on the leading many‐core architectures with contrasting programming models and still achieve the comparable performance results. As an example, we will show that a 2‐year contract with 252 times steps and 1, 000, 000 samples can be priced in approximately one fifth of a second on two leading many‐core architectures. The purpose of this paper is to understand what is required to accelerate the numerical‐intensive algorithms such as the Asian option pricing algorithm in quantitative and how to take advantage of the parallel programming features on many‐core architecture and express parallelism inherent in the similar algorithms in quantitative finance. Copyright © 2015 John Wiley & Sons, Ltd.